Potensi Penggunaan Essential Oil dari Tumbuhan di Indonesia dalam Menurunkan Berat Badan - Prilly Mutiara Sandy (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2021)
Introduction: overweight and obesity are health problems that arise in developing countries. Although classified as a non-communicable disease (NCD), being overweight can cause death due to its comorbidity. Conventional obesity therapy is generally in the form of medications and surgical procedures. If consumed long-term, it will have dangerous side effects and it is invasive, and there is a possibility to relapse. Therefore, this review was aimed to collect all available data on non-invasive therapies in the form of aromatherapy inhalation containing active phytochemical constituents derived from Indonesian plants that will be possible as a natural anti-obesity agent. Methods: The data review during 2007-2021 with electronic searches through Scopus, ScienceDirect, PubMed, and Google Scholar. Articles are sorted by the keywords